La evolución de la memoria de la Guerra Civil en el espacio urbano de Bilbao: una mirada comparativa - Jesús Alonso Carballés (Cahiers de Civilisation Espagnole Contemporaine)
This article’s main objective is to study the institutional politics developed around the memory of the Civil War in the city of Bilbao. Our work is an attempt to develop an «archaeology of memory» which will allow us to study in a chronological fashion the traces left by these politics in the urban spaces of Bilbao, from the erection of the statute of General Mola in June 1937 to the construction of the memorial monument in honor of the victims of Frankism. These case studies also include references to the evolution of this memory in the symbolic villages of Burgos and Valence, in order to offer a comparative view of three key capitals of the 1936 conflict.